Ethical Dilemmas and Principles in Organ Transplantation in China - Zhang 1, Zhen; Zang 2, Zheng (Acta Bioethica, 2021)
In medical clinical practice, organ transplantation is mainly applied to patients with end-stage organ lesions and organ failure. However, with the development of organ transplantation, many ethical issues and controversies have arisen. From the perspective of bioethics, the article compares the relevant ethical and legal regulations of organ transplantation in various countries. Due to the complexity of the real situation, many ethical dilemmas arise in organ transplantation in China. The article analyzes and researches three aspects of organ donation, distribution, and trading, and finds that there are various ethical problems in these three aspects of organ transplantation in China, such as whether the principle of presumed consent is ethical, whether brain death is legalized, the selection and determination of transplant patients, and whether human organ trading is legalized, etc. With the help of the four principles of bioethics and the current development of organ transplantation in China, the article proposes that organ transplantation in China should follow four ethical principles: the principle of respect for life, the principle of do no harm/benefit, the principle of respect for autonomy, and the principle of justice, in order to provide a defense for the legitimacy of organ transplantation.